2010
DOI: 10.1371/journal.pone.0011356
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea Alters Sleep Stage Transition Dynamics

Abstract: IntroductionEnhanced characterization of sleep architecture, compared with routine polysomnographic metrics such as stage percentages and sleep efficiency, may improve the predictive phenotyping of fragmented sleep. One approach involves using stage transition analysis to characterize sleep continuity.Methods and Principal FindingsWe analyzed hypnograms from Sleep Heart Health Study (SHHS) participants using the following stage designations: wake after sleep onset (WASO), non-rapid eye movement (NREM) sleep, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
105
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(117 citation statements)
references
References 32 publications
(61 reference statements)
7
105
2
1
Order By: Relevance
“…For example, survival analysis and similar approaches focusing on sleep stage transition dynamics have been shown to capture fragmentation related to OSA more effectively than standard metrics. [14][15][16] Although the basis for sleep misperception remains uncertain, understanding this phenomenon is important for epidemiological assessments of sleep duration as well as clinical assessment of patient with insomnia. Recent data emphasizes the importance of perception, as the first group to perform objective PSG testing in a large longitudinal cohort clearly demonstrated that health risks such as hypertension, diabetes, and mortality, previously attributed to insomnia symptoms or selfreported short sleep durations, may in fact be mainly attributed to the subset of patients with the combination of insomnia symptoms and objective short TST on PSG.…”
Section: Sleep Fragmentation Does Not Explain Misperception Of Latencmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, survival analysis and similar approaches focusing on sleep stage transition dynamics have been shown to capture fragmentation related to OSA more effectively than standard metrics. [14][15][16] Although the basis for sleep misperception remains uncertain, understanding this phenomenon is important for epidemiological assessments of sleep duration as well as clinical assessment of patient with insomnia. Recent data emphasizes the importance of perception, as the first group to perform objective PSG testing in a large longitudinal cohort clearly demonstrated that health risks such as hypertension, diabetes, and mortality, previously attributed to insomnia symptoms or selfreported short sleep durations, may in fact be mainly attributed to the subset of patients with the combination of insomnia symptoms and objective short TST on PSG.…”
Section: Sleep Fragmentation Does Not Explain Misperception Of Latencmentioning
confidence: 99%
“…We note that characterizing sleep architecture through stage percentage is an insensitive method for capturing sleep fragmentation. 16,21 Therefore, we also investigated bout duration for each sleep stage across these groups. This approach allowed us to assess whether more sensitive measures could support the hypothesis that fragmentation drives misperception.…”
Section: R Esu Lt Smentioning
confidence: 99%
See 1 more Smart Citation
“…OSA is characterised by recurring episodes of upper airway obstruction during sleep [21], intermittent hypoxia [22], sleep fragmentation [23], excessive daytime sleepiness [21] and increased cardiovascular risk [24]. Upper airway collapse during sleep can be prevented by the application of nasal continuous positive airway pressure (CPAP), which is the treatment of choice for moderateto-severe OSA in adults.…”
mentioning
confidence: 99%
“…Another study suggested that sleep efficiency, sleep latency, and N1 did not differ between control group, mild apnea and severe apnea. On the other hand, N2 and REM latency increased with the severity of AHI with the decrease in N3 and REM [14]. Other literature suggests that at least in children sleep architecture do not differ with the position dependent AHI [15].…”
Section: Discussionmentioning
confidence: 76%